(untitled) (Archives of Mechanics - Test, 2013)
We consider the local deformation near a point at the interface between free and fixed boundary segments in an elastic half-plane undergoing plane strain deformations. Using asymptotic analysis, we show that the addition of a reinforcement along the free boundary effectively eliminates the well-known oscillatory behavior of the displacement and stress fields in the vicinity of the point leading to a strong square-root stress singularity. In addition, we demonstrate that the reinforcement induces a deformation field which is smooth locally and bounded at the point of interest.